Dopamine 2 receptor expression in various pathological types of clinically non-functioning pituitary adenomas - Gabalec, Filip; Beranek, Martin; Netuka, David; Masopust, Vaclav; Nahlovsky, Jiri; Cesak, Tomas; Marek, Josef; Cap, Jan (Pituitary, 2012)
Clinically non-functioning pituitary adenomas account for about one-third of pituitary tumors. The majority of them are pathologically classified as gonadotropinomas or null-cell adenomas without hormonal expression. The rest represent silent corticotroph adenomas and plurihormonal tumors. Conservative therapy with dopamine agonists is effective in some cases only depending on the expression of dopamine 2 receptors (D2R). The aim of this study was to quantitatively estimate D2R expression in clinically non-functioning pituitary adenomas and correlate the results with adenoma type according to pathological classification. Out of the 87 adenomas investigated, 63 expressed gonadotropins, 7 were silent corticotroph adenomas, 7 were plurihormonal tumors, and only 6 did not express any pituitary hormone on immunohistochemical investigation. With the use of the reverse transcriptase PCR technique, D2R mRNA was expressed in all adenomas with very heterogeneous quantity. The expression was very low in corticotroph adenomas (relative median quantity after normalization to housekeeping gene 0.01) and lower in plurihormonal tumors (median 0.4) than in gonadotroph (median 1.3) and null-cell adenomas (median 1.9). The difference between corticotroph adenomas and plurihormonal tumors in comparison with other pathological types was statistically significant. The expression of D2R did not depend on the presence or absence of gonadotropins. We conclude that D2R expression is very low in corticotroph adenomas and significantly lower in plurihormonal tumors. The positivity of gonadotropins does not predict the D2R quantity.